Ileosigmoid Knotting: Analysis of Patients Clinical Profiles and Determinants of Outcomes. (24th July 2020) - Abebe, Kirubel; Sherefa, Kalid; Teshome, Henok; Abebe, Engida
Abstract : Introduction . Ileosigmoid knotting (ISK) is an uncommon form of bowel obstruction due to wrapping of the ileum or sigmoid colon around the base of the other. It is associated with poor prognosis. Data on ISK are scarce in our country. The aim of this study was to assess clinical profiles, management, and outcome of patients operated for ISK. Methodology . A retrospective analysis of all patients operated for ISK at St. Paul's hospital millennium medical college (SPHMMC) from February 2014 to January 2020 was performed. Results . A total of 28 patients (M: F  = 3 : 1) were studied. The mean age was 41.7 years (SD ± 19.5) and ranged from 18 to 80 years. The mean duration of illness was 1.6 days (SD ± 1.1). Abdominal pain and vomiting were seen in all patients followed by abdominal distention (24, 85.7%) and failure to pass feces or flatus (23, 82.1%). Preoperative diagnosis was correct in 6 (21.4%) patients. Almost all patients (26, 92.8%) had gangrenous bowel. The commonest procedure performed was resection of the gangrenous segments with primary ileoileal anastomosis and sigmoid end colostomy (16, 57.1%). Complications were seen in 11 (39.3%) patients and the commonest being surgical site infection (SSI) (7, 25%). Death occurred in 6 (21.4%) patients, and it was significantly (p = 0.020 ) associated with intraoperative shock (systolic blood pressure (SBP) < 90 mmHg). Conclusion . ISK lacks specific clinical features and imposes a significant rate of bowel strangulation, which deserves high index of suspicion and urgent laparotomy. The choice of surgical procedure should be determined by intraoperative bowel status and patients' general condition.